Linear response of the Greenland ice sheet's tidewater glacier terminus positions to climate - Dominik Fahrner; James M. Lea; Stephen Brough; Douglas W. F. Mair; Jakob Abermann (Journal of Glaciology, 2021)
Gaining knowledge of tidewater glacier (TWG) margin evolution, solid ice flux and their responses to climate over large spatio-temporal scales provides valuable context for the projection of future Greenland ice sheet (GrIS) change. Although studies of sector-wide responses of TWGs exist, studies at an ice-sheet-wide scale have only just become feasible. Here, we present a dataset of 224 annual TWG margins for 1984–2017 (n = 3801), showing that averaged over regional scales, normalised terminus change is linear. Regionally linear retreat trends were identified across most sectors of the GrIS starting in the mid-1990s, although in contrast to previous studies, the northeastern sector is shown to have experienced sustained retreat since the mid-1980s. Through cointegration analyses, individual glaciers are shown to have differing sensitivities to potential climate drivers, though on a sector-wide scale the northwest and southeast are shown to be especially sensitive to annual sea surface temperature and June–July–August air temperature, respectively. Although 92% of the analysed glaciers experience retreat across the GrIS, observed increases in absolute flux for the entire ice sheet can be explained by changes in just 11 of these TWGs.